NEW REFORMS IN UZBEKISTAN - Yusupova Shukrona (Лучшие интеллектуальные исследования, 2024)
Today, Uzbekistan is the most beautiful and unique country for all of us dear mother is our Motherland. The world of practical and rapid development in Uzbekistan is being recognized by the community. It was a land of noble renewal Uzbekistan is a source of pride for all young people. Now It is traveling over Uzbekistan. This is the fun of tomorrow He works with enthusiasm and enthusiasm. Action strategy well-known scientists of the world recognized today the significant changes that are being implemented, They say that even the experts who share their full views have a doubtful perspective is evaluating. In the first year of his presidency, the head of the republic is different sought to make the state more open to predictions and the result is manifested in our daily life.